Pengaruh Formulsi Nutrisi Hidroponik pada Sistem Drip Terhadap Pertumbuhan dan Potensi Hasil Melon - Darmawan, Ahmad Arif; Dinarto, Wafit; Widodo, Dwi Agus (Savana Cendana, 2024)
The study aimed to determine the growth and yield of melon using a hydroponic drip irrigation system with the nutritional formulation AB Mix manufacturer and AB Mix self formulation. The research was carried out in the Banaran plastic house, Somokaton, Ngluwar, Magelang. This study was a single-factor experiment arranged in a Completely Randomized Design (CRD) with two replications. The treatments tested consisted of two types of nutritional formulas, namely concoction AB mix and manufactured AB mix. Data were analyzed by independent sample t-test at a 5% significance level. The results showed that the growth of melon plants fed with AB mixed nutrition and manufactured AB mix was not significantly different, except for the number of leaves. The yield parameters showed that the weight and diameter of the melon fruit in the plants that were given the AB mix self formulation were higher than the AB mix of the manufacturer. But the thickness of the fruit flesh and the sugar content in the plants that were given with the AB mixed nutrition were higher than the AB mix self formulation.